PENGEMBANGAN PERANGKAT PEMBELAJARAN MODEL INVESTIGASI KELOMPOK (GROUPS INVESTIGATION) PADA MATERI GELOMBANG BUNYI DI SEKOLAH MENENGAH PERTAMA - Aras Larasati; Muhammad Nasir; Muhammad Sahal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The learning tool developed is a group investigation model learning device (Groups Investigation) on sound wave material for junior high school students, consisting of a Lesson Plan (RPP), Student Worksheet (LKPD), and Learning Outcomes Test. Learning Science Physics and validating learning tools for the Group Investigation model (Groups Investigation) on sound wave material. This type of research is Research and Development (R&D) with a 4-D model design. The research instrument used is the RPP validation assessment sheet, LKPD and Learning Outcomes Test which is used by validators to assess learning tools. Data analysis in this researcher uses descriptive analysis, in a way calculate the validity score of each learning indicator. The average validity of the LKPD is 3.3 with a very high category. the average validity of the Learning Outcomes Test is 3.4 with a very high category, so that the overall average of learning tools is 3.36 with a very high category. Thus, the learning device for the Natural Sciences Physics model of the group investigation (Groups Investigation) is declared valid and suitable for use in sound wave material for junior high school students.Keywords: Physics science learning tools, Group Investigation model(Groups Investigation)